Exploring the computer algebra system as a tool in learning the fundamental of column buckling behavior for civil engineering students / S.F.Senin, R.Rohim and A.Yusuff - Senin, S.F.; Rohim, R.; Yusuff, A. (2022)
This paper presents the symbolic buckling analysis of an elastic column structure using Maple, a symbolic computer algebra system (CAS). The symbolic analysis was used as a learning tool in the third year of the undergraduate civil engineering programme at the School of Civil Engineering, Universiti Teknologi MARA Pulau Pinang Branch, Permatang Pauh Campus. The students were interviewed after using the symbolic buckling analysis and it was found that they were able to understand, justify their predictions and better visualise the solutions of the given problems. The tool serves as a new method for learning and understanding the basic behaviour of an elastic column structure made of any material and under a freely specified boundary condition at both ends under a concentric compressive load. Instructors should be trained in the use of the CAS software to train our future civil engineering graduates for the industrial markets.